Non – Operative Treatment Outcome of Hematogenous Osteomyelitis of the Femur in Infants: A Case Series - Iman Dwi Winanto; Yudha Satria (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Introduction: Osteomyelitis is a bacterial infection involving bone, its marrow, and the adjacent structures. The most common mechanism of infection in children is hematogenous, thus called hematogenous osteomyelitis (HO). There is an absolute requirement of antibiotic therapy. Surgery is considered in some cases. This is a report presenting 2 cases of distal femur HO in infants treated non – operatively with intravenous antibiotic alone. Case Presentation: Case 1: A one month old male infant was admitted due to swollen knee with pus producing sinus on the medial side for the last one month, without any systemic manifestation. Laboratory showed leucocytosis and increased erythrocyte sedimentation rate (ESR). Cytology showed granulomatous inflammation. Plain radiograph showed bone destruction with periosteal reaction and MRI showed heterogenic hyperintense lesion with penumbra sign on the distal femur. Intravenous Ampicillin Sulbactam 225 mg/6h and Amikacin 50 mg/24h were given for 7 days were given, continued with oral of Co-Amoxiclav 3 x 2.5 mg/ day for another week. The patient showed marked clinical and laboratory improvement after therapy; Case 2: A three-month old male infant with similar sign and symptoms was admitted, but it was on the right limb. Laboratory showed leucocytosis, increased ESR, and increased C-reactive protein (CRP). Plain radiograph and MRI examinations showed similar results with the first case. Intravenous Ceftriaxone 350 mg/12h for 7 days, continued with Cefadroxil 2 x 150 mg / day for another week was given. The similar clinical and laboratory outcomes with the first were achieved. Discussion: Whether or not surgical intervention is required, the successful treatment of all forms of osteomyelitis requires appropriate antibiotic therapy. Studies have shown that appropriate antibiotic therapy alone without surgical intervention may suffice for 90% of cases of HO. In some cases of complicated HO, surgical incision and drainage (including multiple procedures) may be indicated. Conclusion: HO in infant patients may be adequately treated by antibiotic alone with satisfactory result. Drug of choice, course of administration, and duration of treatment are important factors. Nevertheless, surgery should also be considered in a failed conservative treatment.